Pola Pendidikan Rasulullah Shallallahu ‘Alaihi Wasallam Sebagai Pendidik Ideal - Sulaiman, Abd. Hamid (Universitas Muslim Indonesia, 2021)
This article discusses the pattern of education of the Prophet sallallaahu 'alaihi wasallam which is the foundation of education, especially Islamic education. The success of education applied by the Prophet Muhammad SAW, both in Makkah Al-Mukarramah approximately 13 (thirteen) years, and in Madinah Al-Munawwarah approximately 10 (ten) years, because of what he conveyed, he has applied first in all aspects of his life and his life. The education or teaching of the Prophet sallallaahu 'alaihi wasallam uses educational patterns, such as: Dialogue Pattern, Repetition Pattern, Praga Giving Pattern, Experiment Pattern, Problem Solving Pattern, Discussion Pattern, Joy Giving Pattern, and Sanction Giving Pattern.